Rockfall Hazard and Risk Assessment Along a Transportation Corridor in the Nera Valley, Central Italy - Guzzetti, Fausto; Reichenbach, Paola; Ghigi, Silvia (Environmental management (New York), 2004)
Rockfalls are a common type of fast-moving slope failures, and in many countries they represent the primary cause of landslide fatalities. We present a methodology to ascertain rockfall hazard and to determine the associated risk along transportation networks. The proposed methodology is based on the combined analysis of the recurrence of rockfall events, determined from historical information, the frequency-volume statistics of rockfalls, obtained from inventories of recent rockfall triggering events, and the results of a physically based, spatially distributed rockfall simulation model used to determine rockfall hazard. The available information on rockfall hazard is combined in a Geographic Information System with a map of the transportation network to identify the road sections potentially subject to rockfalls. Information on the location and type of rockfall defensive measures, including revetment nets, elastic fences, concrete walls, and artificial tunnels, is used to estimate the efficacy of the defensive structures and to determine the level of the residual rockfall risk along the roads. To illustrate the methodology, we discuss an application in a 48-km2 area in the Nera River valley, in the Umbria Region of central Italy, where rockfalls are abundant, and where considerable investments were recently made to mitigate rockfall risk.